The devil and other stories eaudiobook - Tolstoy, Leo (Recorded Books Inc., 2014)
This collection of eleven stories spans virtually the whole of Tolstoy's creative life. While each is unique in form, as a group they are representative of his style, and touch on the central themes that surface in War and Peace and Anna Karenina. Stories as different as "The Snowstorm", "Lucerne", "The Diary of a Madman", and "The Devil" are grounded in autobiographical experience. They deal with journeys of self-discovery and the moral and religious thought that characterizes Tolstoy's works of criticism and philosophy. "Strider" and "Father Sergy", as well as reflecting Tolstoy's own experiences, also reveal profound psychological insights. These stories range over much of the nineteenth-century Russian world, from the nobility to the peasantry, the military to the clergy, from merchants and cobblers to a horse and a tree. Together they present a fascinating picture of Tolstoy's skill and artistry. About the Series: For over 100 years Oxford World's Classics has made available the broadest spectrum of literature from around the globe. Each affordable volume reflects Oxford's commitment to scholarship, providing the most accurate text plus a wealth of other valuable features, including expert introductions by leading authorities, voluminous notes to clarify the text, up-to-date bibliographies for further study, and much more.